La visione di mania umana e divina in Platone (The concept of divine and human “mania” in the Platonic dialogues) - Głodowska, Anna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2013)
In this article will be discussed the passages of the Platonic dialogues that give information about the way in which the philosopher understood the term “mania”. Particularly important is the reflection on this subject contained in Phaedrus in which different kinds of madness were distinguished and briefly characterized. Especially the essential is the concept of poetic inspiration because it takes an important place in Plato’s theoretical and literary thought. It had also a significant influence on shaping his opinions on the subject of poets and their work. The Plato’s term of poetic inspiration and connected with it the issues of literary output and its reception make the fundamental part of this article.